Modelling Institutional Change in the Payments System and its Implications for Monetary Policy - Capie, F; Tsomocos, D; Wood, G (Routledge, 2006)
Focusing on the interdependence of institutional change in the payments system and monetary policy, this book examines the different channels via which payment systems affect monetary policy. It is intended for researchers and practitioners in the field of monetary economics.